Aktivitas Antioksidan Herba Kate Mas (Euphorbia heterophylla L.) terhadap Radikal DPPH (1,1-Difenil-2-Pikrilhidrazil) - Louis Madalena; Titik Sunarni; Fransiska Leviana (Jurnal Farmasi Indonesia, 2010)
Antioxidant is very important to keep human’s health because of it can scavenge free radical. Flavonoid is usual natural antioxidant got on plants. Euphorbia heterophylla L. which is used by people as traditional herbal medicine and it has traditional name kate mas is known contain of flavonoid, tannin and saponin. The aim of the experiment was to find out the antioxidant activity of kate mas (Euphorbia heterophylla L.) herb and the potency of methanolic extract, hexane, etil acetat and water fractions, and also of kate mas herb on DPPH (2,2-difenil-1-pikrilhidrazil) radical with IC50 parameter. Kate mas herb were extracted by maceration method using methanol. The obtained extract was partitioned with water and hexane, and then with etil acetat. The antioxidant activity of the obtained fraction was tested against DPPH radical. The test was conducted in 4 series of concentrations by adding 4.0 ml test solutions with 1.0 ml DPPH 0.45 mM. The radicals scavenging activity was measured with spectrophotometer at 515 nm wavelength and determined the IC50 value. The experiment used rutin as positive control. The result of the experiment showed that kate mas herb had antioxidant activity with IC50 of methanolic extract, water fraction, n-hexane fraction, and etil acetat fraction: 44,43 ppm; 130,63 ppm; 212,81 ppm; and 5,88 ppm respectively. The etil acetat fraction has the strongest activity compairing to the other with the IC50 is almost near often rutin’s IC50 is 5,11 ppm as the positif control.